2020
DOI: 10.1080/10962247.2020.1729277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corn stover particle size and C/N ratio on reactor performance in solid-state anaerobic co-digestion with dairy manure

Abstract: Green energy generation from agricultural waste has the potential to minimize dependency on fossil and reduce the resultant environmental impact of this fuel provided anaerobic reactor performance is optimized. Hence, the interactive impact of carbon to nitrogen (C/N) ratio, particle size, and codigestion of dairy manure (DM) and corn stover (CS) on solid-state anaerobic digester (SSAD) performance was investigated with four treatments (DMCS24S, DMCS24L, DMCS28L, and DMCS32L) in this solid-state study. Novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 54 publications
6
6
0
1
Order By: Relevance
“…For oDMBY and oDMMY, their optimum yields were recorded at the same temperature and hydraulic retention time but with different particle sizes. Optimum oDMBY was recorded at a particle size of 4 mm, and this result agrees with what was recorded by earlier researchers when compared with 6 mm particle size (Ajayi-Banji et al, 2020; Kirby et al, 2020; Kulichkova et al, 2020; Prade et al, 2019). Compared with 2 mm particle size, it is contrary to what was earlier reported (Naegele et al, 2014; Nalinga and Legonda, 2016).…”
Section: Resultssupporting
confidence: 91%
“…For oDMBY and oDMMY, their optimum yields were recorded at the same temperature and hydraulic retention time but with different particle sizes. Optimum oDMBY was recorded at a particle size of 4 mm, and this result agrees with what was recorded by earlier researchers when compared with 6 mm particle size (Ajayi-Banji et al, 2020; Kirby et al, 2020; Kulichkova et al, 2020; Prade et al, 2019). Compared with 2 mm particle size, it is contrary to what was earlier reported (Naegele et al, 2014; Nalinga and Legonda, 2016).…”
Section: Resultssupporting
confidence: 91%
“…A similar result was obtained by Ajayi-Banji et al [45] when evaluating SS-AD using corn stover and dairy manure. These authors also reported the better performance of high-solid digestion systems when reducing the C/N ratio of the mixture, with these systems favoring the alkalinity and pH values of the reactor leachate.…”
Section: Commercial Technologies For Ss-adsupporting
confidence: 87%
“…Solid-state fermentation has been successfully studied for producing enzymes, biosurfactants, proteins, and biofuels [39,40] and a great variety of valuable products [41][42][43][44]. Anaerobic digestion has also been evaluated under this configuration and the co-digestion of different residues, such as manure, food wastes, and agricultural wastes, has also been studied under SS-AD conditions [45][46][47].…”
Section: Solid-state Anaerobic Digestion (Ss-ad)mentioning
confidence: 99%
“…They suggested that the low CH 4 yield (in the case of a 1-mm chopped crop) may be attributed to the less lactic acid generation during ensiling. A similar result was observed in the case of corn stover; when the particle size was reduced from 0.42-0.84 to 0.18-0.42 mm, significantly lower methane and biogas yields could be observed (Ajayi-Banji et al, 2020). In addition, a digester can be easily clogged in the case where fine particles are fed, which should be carefully considered in the design.…”
Section: Particle Sizesupporting
confidence: 71%